ANALISIS SEKTOR UNGGULAN KABUPATEN TOLITOLI DAN KABUPATEN BUOL - Kawulusan, Supomo (Katalogis, 2013)
The purpose this reseach the economy sector growth classification in Tolitoli and Buol regency area, to know basis and non-basis sectors of the economy sector growth in Tolitoli and Buol regency area, to know the change and movement in economic sector into Tolitoli and Buol regency and to determine the economic advantageÂ  sector in Tolitoli and Buol regency. Based on the account result which is obtained indicate that growth classification of economic sector in Tolitoli and Buol regency which is progress and developed sector is agriculture sector that progress but still stagnant sector that are cultivation industry sector and potential sector or still developing that are electric and water clean sectors and underdeveloped sectors that are mining and digging, building, trade, hotel and restaurant, transport and communication, finance, rental and company and services sectors. The including of in basis sector for Tolitoli and Buol regency that are agriculture and cultivation industry sectors. The result of shift share analysis indicate that the sector has got the quick growth process so that has potential to be developed into PDRB growth in Tolitoli regency that are electric, water, rental and company services sectors. But in Buol regency that are agriculture, electric, water clean, transport and communication sectors. The including as the advantage sector and the big contribution sectors on PDRB in Tolitoli and Buol regency that are agriculture, service sector, trade, hotel, restaurant and cultivation industry sectors.